Formats for monitoring project implementation: Proposals for the Kenya Livestock Development Project - International Livestock Centre for Africa (International Livestock Centre for Africa, 1978)
Proposals for monitoring the disbursements and implementation of the Kenya Livestock Development Project, phase II, and evaluation of present data collecting systems w. respect to main project components.